The role of weight stigma in weight regain in bariatric surgery - Himmelstein, Mary S.; Knepp, Kristen A.; Phelan, Sean M. (Frontiers in Endocrinology, 2022)
Obesity is highly stigmatized, and individuals who undergo bariatric surgery are subject not only to weight stigma, but also to stigma related to the procedure itself. Patients lost to follow-up after surgery make estimating the amount of regain occurring after surgery difficult, and often patients fail to follow up due the shame of weight regain. Patients report difficulty following the diet necessary to maintain weight loss. Additionally, when they seek support after surgery, they often encounter stigmatizing messaging related to weight. Weight bias internalization, weight stigma, and stigma about having the surgery all contribute to feelings of social isolation, disordered eating, and reduced motivation to engage in physical activity. In this chapter, we present evidence for the impact of stigma on bariatric surgery outcomes and discuss the behavioral, physiological, and emotional processes that contribute to weight regain.